Seasonal variability in phytoplankton stable carbon isotope ratios and bacterial carbon sources in a shallow Dutch lake. (26th June 2017) - Lammers, J. M.; Reichart, G. J.; Middelburg, J. J.
Abstract: Ecosystem metabolism of lakes strongly depends on the relative importance of local vs. allochthonous carbon sources and on microbial food‐web functioning and structure. Over the year ecosystem metabolism varies as a result of seasonal changes in environmental parameters such as nutrient levels, light, temperature, and variability in the food web. This is reflected in isotopic compositions of phytoplankton and bacteria. Here, we present the results of a 17‐month study on carbon dynamics in two basins of Lake Naarden, The Netherlands. One basin was restored after anthropogenic eutrophication, whereas the other basin remained eutrophic. We analyzed natural stable carbon isotope abundances ( δ 13 C) of dissolved inorganic carbon, dissolved organic carbon and macrophytes, and combined these data with compound‐specific δ 13 C analyses of phospholipid‐derived fatty acids, produced by phytoplankton and bacteria. Isotopic fractionation ( ε ) between phytoplankton biomass and CO2(aq) was similar for diatoms and other eukaryotic phytoplankton, and differences between sampling sites were small. Highest ε values were observed in winter with values of 23.5 ± 0.6‰ for eukaryotic phytoplankton and 13.6 ± 0.3‰ for cyanobacteria. Lowest ε values were observed in summer: 10.5 ± 0.3‰ for eukaryotic phytoplankton and 2.7 ± 0.1‰ for cyanobacteria. The annual range in δ 13 Cbact was between 6.9‰ and 8.2‰ for the restored and eutrophic basin, respectively, while this range was between 11.6‰ and 13.1‰ for phytoplankton in the restored and eutrophic basin, respectively. Correlations between δ 13 Cphyto and δ 13 Cbact were strong at both sites. During summer and fall, bacterial biomass derives mainly from locally produced organic matter, with minor allochthonous contributions. Conversely, during winter, bacterial dependence on allochthonous carbon was 39–77% at the restored site, and 17–46% at the eutrophic site.